CHALLENGES FACED BY EFL STUDENTS IN ACADEMIC WRITING - Feruza Abdumajidova; Lola Xayrulloyeva Dilshod qizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
Academic writing is widely regarded as one of the most complex and cognitively demanding skills in Second Language Acquisition (SLA), especially for English as a Foreign Language (EFL) learners at the tertiary level. This study presents a detailed and systematic analysis of the major challenges encountered by EFL students when producing academic texts in English. The paper integrates findings from a wide range of international studies conducted between 2000 and 2023, highlighting linguistic deficiencies, organizational limitations, and psychological constraints. The primary objective of this research is to identify the root causes of students’ writing difficulties and examine how these challenges influence their academic performance and overall language development. Special attention is given to the relationship between lexical competence, grammatical accuracy, critical thinking, and writing proficiency. The findings demonstrate that EFL students often experience a significant gap between their cognitive ideas and their ability to express them effectively in written English. High-achieving learners tend to employ a diverse set of writing strategies, including pre-writing planning, drafting, revising, and metacognitive monitoring, while low-achieving students frequently rely on surface-level strategies such as direct translation and rote memorization. The study concludes that explicit instruction, continuous formative feedback, and strategy-based pedagogy are essential for improving academic writing skills and bridging the gap between language knowledge and written performance.